PENGARUH MEDIA WORDPRESS BLOG TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 6 PALEMBANG - Nia Kurnia; Dewi Koryati; Rusmin AR (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This study is intended to look at the differences in the influence of wordpress blog media with SlideShare media on the students’ learning outcomes on economics subjects at SMAN 6 Palembang. It uses is a “Quasi-experimental method” in the form of “Nonequivalent control group design”. The study population were students of class X IIS SMA Negeri 6 Palembang of the odd semester of academic year 2014/2015 consisting of four classes, namely X IIS.1, X IIS.2, X IIS. 3, and X IIS.4 the number of 107 learners. Sampling technique using cluster random sampling and obtained two classes of class X IIS.1 as an experimental class numbering 26 students and X IIS 2 as the control class numbering 27 students. The test is used to collect data on learning outcomes before and after the use of media and media SlideShare wordpress blog. For mengalisis used t-test with significance level (α = 0.05). T test results showed that the value of t = 3.03, while table = 1.99, meaning in this study Ha accepted. Based on these results, it is suggested media wordpress blog can be used as a medium of learning by teachers to improve student learning outcomes. To overcome the disadvantages of the application of the media when it is difficult to connect to the Internet, it must open a wordpress blog through a database owned laptop in offline.